NURSING SERVICE AND INPATIENT SATISFACTION LEVELS AT THE COMMUNITY HEALTH CENTER: A CROSS-SECTIONAL STUDY - Fakhrun Nisa’ Fiddaroini; Nanang Bagus Sasmito; Karisma Dwi Ana; Putu Dewi Novita (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: One factor that influences patient satisfaction is nursing services. Nursing services can be measured through five indicators are attention, acceptance, communication, cooperation, and responsibility. Objectives: This study aims to determine the relationship between nursing services and inpatient satisfaction levels at the Pandaan Community Health Center in Pasuruan Regency. Methods: The method of this study correlates with a cross-sectional approach. Data were collected from a sample of 40 respondents over one month. The Nursing Services Questionnaire and the Inpatient Satisfaction Levels Questionnaire were used to measure the study variable. Data was analyzed using Spearman’s rank test and the order correlation test to determine the strength and direction of the association between the two variables. Results: The results showed that nursing services are in the good category, with 26 respondents (65%), and inpatient satisfaction levels are in the high category, with 27 respondents (67.5%). There was a relationship between nursing services and inpatient satisfaction levels in Pandaan Community Health Center in Pasuruan Regency (ρ = 0.000 and r = 0.643), indicating a positive correlation, a moderate level of relationship strength, and a correlation between the two variables. Conclusion: This study indicates that the quality of nursing services directly affects patient satisfaction. Therefore, nursing staff should focus on improving service quality through effective therapeutic communication, prompt responses to patient needs, and demonstrating empathy and professionalism in every nursing action. Future research could employ a quasi-experimental design to assess the impact of nursing service training on improving patient satisfaction.